The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00027-007-0876-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upstream hydropower operation and oligotrophication on the light regime of a turbid peri-alpine lake

Abstract: Anthropogenic activities in catchments can alter the light regimes in downstream natural waters, affecting light attenuation and the perceived optical properties of the waters. We analyzed the effects of upstream hydropower operation and oligotrophication on light attenuation and reflectance in Lake Brienz (Switzerland). For this purpose, we reconstructed its light regime for the pre-dam condition and for periods of 4-fold increased primary productivity, based on direct observations of light and beam attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The right side of equation (7) describes the empirical relation between measured K 0 and s d . Jaun et al (2007) determined k 1 = 0.22 m -1 and k 2 = 0.69 for intense turbidity periods (May to September) and k 1 = 0.11 m -1 and k 2 = 0.61 for reduced turbidity periods (October to April). For a given K 0 , the corresponding light profile in the lake for the instant global radiation is given by:…”
Section: Estimation Of Primary Production In Clear Watermentioning
confidence: 93%
See 3 more Smart Citations
“…The right side of equation (7) describes the empirical relation between measured K 0 and s d . Jaun et al (2007) determined k 1 = 0.22 m -1 and k 2 = 0.69 for intense turbidity periods (May to September) and k 1 = 0.11 m -1 and k 2 = 0.61 for reduced turbidity periods (October to April). For a given K 0 , the corresponding light profile in the lake for the instant global radiation is given by:…”
Section: Estimation Of Primary Production In Clear Watermentioning
confidence: 93%
“…Moreover, the operation of the hydropower reservoirs has decreased turbidity in Lake Brienz in the summer through particle retention, and increased turbidity during winter through hydropower production . Based on these findings, Jaun et al (2007) concluded that the altered particle dynamics led to a doubling of light attenuation during winter and a reduction of~50 % during summer.…”
Section: Lake Brienzmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the particle budget in Lake Brienz (Finger et al, 2006) and past Secchi depth records, Jaun et al (2007) reconstruct the light attenuation for the last decades and the early 1920s. As a result of the hydropower operation, Lake Brienzs PAR attenuation was~twice as strong in summer under pre-dam conditions, whereas it is now~twice as strong in winter compared to the pre-dam conditions.…”
Section: Lake Brienz and Its Catchmentmentioning
confidence: 99%